Credit Growth in Latin America : Financial Development or Credit Boom? - Hansen, Niels-Jakob (IMF Working Papers; Working Paper ;, 2013)
Banking credit to the private sector in Latin America has on average increased by 7 percent of GDP from primo 2004 to ultimo 2011, with real credit in some countries growing by up to 20 percent per year. This paper documents and analyzes the patterns of credit growth in 18 countries in Latin America and uses econometric methods to determine whether it is indicative of financial deepening or poses risks of credit booms. The strongest credit growth occurred for consumption and mortgages within the household sector and for construction within the corporate sector. At the same time credit has de-dollarized in most countries and there are some signs of maturity lengthening. To assess whether the recent credit growth is excessive two different methods are applied. First, by application of HP-filters the paper finds that credit-to-GDP levels in a number of countries are above their long-term trend. Second, using a panel co-integration approach on 107 high and mid-income countries the paper estimates a model for the credit-to-GDP levels. Comparing the actual levels of credit with the ones predicted by the model we find that some countries in Latin America show significant and positive deviations. These results indicate the existence of a certain level of risk in the recent credit developments.